Deforestation impact on discharge regime in the Doce River Basin - Lyra,Barbara Ucelis (2019)
Abstract The construction of scenarios using hydrological models can evaluate the hydrological response in watersheds, due to changes in the soil use. In this context, this study analyzed the consequences of deforestation in the hydrological behavior of the Doce River Basin, which has a drainage area of ​​approximately 86.715 km². The basin presents problems regarding water availability, floods, indiscriminate deforestation and inadequate soil management. The Model of Large Basins (MGB-IPH) was selected, using daily data from 1990 to 2014, 11 fluviometric, 81 rainfall and 12 meteorological stations, numerical model of the land, soil maps, and use and land cover. Hydrological modeling was performed in the following steps: calibration of parameters (1990 and 2005), validation (2006 to 2014) and simulation of deforestation scenarios (2000 to 2014). It was observed that the replacement of forests by pasture caused reductions in the average annual flows, indicating a decrease in average flows in deforestation scenarios. As for the behavior of floods, deforestation caused them to increase, while the annual minimum flows reduced with deforestation. The results demonstrate the worsening that the simulated scenarios can cause in the problems already found in the basin, such as floods and water shortages, to supply the uses for which the basin is intended.